Effect of work-related events on depressive symptoms in Japanese employees: a web-based longitudinal study - NISHIMURA, Yuki (Ind Health, 2020)
While a number of work-related events have been proposed as risk factors for depression, a majority of studies have focused only on a few events in a single study. Therefore, we conducted a web-based longitudinal study to comprehensively investigate the impact of various work-related events on depressive symptoms. Ten thousand Japanese workers representing the Japanese working population were recruited online and questioned on their experiences of 36 work-related events in the past year. Their depressive symptoms were also assessed based on the Center for Epidemiologic Studies Depression Scale. Two years later, 3,098 participants responded to a follow-up study. By excluding 1,030 participants who were classified as being depressed in the baseline survey, data of 2,068 participants were analyzed. Odds ratios (OR) were calculated using multivariate logistic regression to assess the effect of work-related events on depressive symptoms. Sixteen events were found to be risk factors and were sorted into four types as follows: experience of an accident or disaster (OR: 4.78–7.67), excessive responsibility (OR: 3.01–3.62), drastic change in workstyle or workload (OR: 2.38–3.08), and interpersonal conflict (OR: 2.41–11.16). The current results, including magnitude relationship of ORs, should be utilized for promoting psychosocially healthy work environment.